Faktor Yang Mempengaruhi Struktur Modal Perusahaan Property, Real Estate And Building Construction - Chandra, Andhika; Sufiyati, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this research is to examine the effect of profitability, liquidity, firm size, and active structure on capital structure in property, real estate and building construction companies on the Indonesia Stock Exchange for the period 2017-2020. The sample was selected by using a purposive method and there were 16 companies that were sampled in this research. This research uses Eviews 10. The results of this research indicate that firm size has significant effect on capital structure. The result of this research indicate that profitability, liquidity and active structure do not have a significant effect on capital structure. The implication of this study is need the role of firm size to make it easier for company to obtain fund in the form of debt loan that increase the value of capital structure, that be used for increase the performance of company.